Validity and reliability of the Evidence Utilisation in Policymaking Measurement Tool (EUPMT) - M. H. Imani-Nasab; B. Yazdizadeh; M. Salehi; H. Seyedin; R. Majdzadeh (Health Research Policy and Systems, 2017)
Abstract Background As a well-known theory in studying the effective factors on behaviour, the theory of planned behaviour (TPB) is frequently used in evaluating the health behaviour of people and healthcare providers, but rarely applied in studying the behaviour of health policymakers. The aim of the present study is to design and validate a TPB-based measurement tool for evidence utilisation in health policymaking (the EUPMT) through a mixed approach using confirmatory factor analysis. Methods The study population consisted of all the specialised units and their employees in the five deputies of Iran’s Ministry of Health and Medical Education in 2013. All those eligible were invited to participate in the study, which comprised 373 persons. The reliability of the EUPMT was determined through test-retest and internal consistency. Additionally, its validity was determined by face, content, convergent, discriminant and construct validities. SPSS-20 and LISREL-8.8 were employed to analyse the data. To assess the fitness of the measurement models, three groups of indices were used, i.e. absolute, relative and parsimonious. Results The content and face validities of the tool were 83% and 67%, respectively. Cronbach’s alpha of different constructs ranged from 0.7 to 0.9. In the test-retest method, the intra-class correlations were between 0.75 and 0.87. Confirmatory factor analysis showed that the penta-factorial structure of the experimental data had acceptable fitness with the TPB (GFI = 0.86, NFI = 0.94, RSMEA = 0.075). Conclusion TPB is able to explain the behaviour of evidence utilisation in health policymaking. The finalised TPB-based tool has relatively good reliability and validity to assess evidence utilisation in health policymaking. The EUPMT can be applied to determine the status quo of evidence utilisation in health policymaking, whilst designing interventions for its improvement and assessing their outcomes.